Selective synthesis of renewable bio-jet fuel precursors from furfural and 2-butanone via heterogeneously catalyzed aldol condensation - Chottiratanachote, Atikhun; Suttipong, Manaswee; Rashid, Umer; Parasuk, Vudhichai; Kondo, Junko Nomura; Yokoi, Toshiyuki; Alsalme, Ali; Ngamcharussrivichai, Chawalit (Multidisciplinary Digital Publishing Institute, 2023)
This study aims to synthesize α,β-unsaturated carbonyl compounds with branched structures via aldol condensation of furfural and 2-butanone using magnesium–aluminum (MgAl) mixed oxides as heterogeneous acid–base catalysts. Regarding the molecular structure of 2-butanone, there are two possible enolate ions generated by subtracting the α-hydrogen atoms at the methyl or methylene groups of 2-butanone. The branched-chain C9 products, derived from the methylene enolate ion, can be applied as bio-jet fuel precursors. The most suitable catalyst, contributing the highest furfural conversion (63%) and selectivity of the branched-chain C9 products (77%), is LDO3, the mixed oxides with 3:1 Mg:Al atomic ratio, with a high surface area and a large number of medium basic sites. The suitable reaction conditions to produce the branched-chain C9 ketones are 1:5 furfural:2-butanone molar ratio, 5 wt.% catalyst loading, 120 °C reaction temperature, and 8 h reaction time. Additionally, this study investigates the adsorption of 2-butanone onto a mixed oxide using in situ Fourier transform infrared spectroscopy; the results of which suggest that the methylene enolate of 2-butanone is the likely dominant surface intermediate at elevated temperatures. Accordingly, the calculation, based on density functional theory, indicates that the methylene enolate ion of 2-butanone is the kinetically favorable intermediate on an MgO(100) as a model oxide surface.